HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN MOTORIK ANAK DI TK ABA WILAYAH PANEMBAHAN KRATON, YOGYAKARTA - Ratu Zilan Fitri Nabila; Siti Arifah (Rena Cipta Mandiri, 2026)
Children are social individuals in the golden period, a critical stage of growth and development, particularly motor development, which is strongly influenced by parenting styles. Appropriate parenting plays an important role in optimizing children’s development. This study aims to determine the relationship between parenting styles and motor development of children at TK ABA Panembahan Kraton Area, Yogyakarta, as specific studies at the local kindergarten level are still limited. The research used a non-experimental descriptive correlational design with a cross-sectional approach. The independent variable was parenting style, and the dependent variable was children’s motor development. Data were collected simultaneously using questionnaires and developmental assessment sheets and analyzed using the Spearman Rank test. Respondents were selected based on inclusion criteria, namely children aged 4–6 years who were active students and parents/guardians willing to participate. The results showed that most parents applied democratic parenting (71.58%), and all children in this group had appropriate motor development. Authoritarian parenting was applied by 15.79% of parents and permissive parenting by 12.63%; in these groups, some children showed doubtful development, although the majority remained appropriate. No motor development deviations were found. The Spearman Rank test indicated a significant positive relationship (p = 0.000; r = 0.528) with moderate strength, concluding that there is a relationship between parenting styles and children’s motor development.